THE ASSESSMENT MODELS OF AIR POLLUTION DURING TRANSPORTATION OF BULK CARGO - Biliaiev, M. M.; Oladipo, M. O. (Science and Transport Progress, 2016)
Purpose. The scientific work is concentrated on development of 3D, 2D numerical models for the prediction of atmospheric pollution during transport of bulk cargo in the railway car. Methodology. To solve this problem numerical models were developed, based on the use of the motion equations of inviscid incompressible fluid and mass transfer, to determine the field of wind velocity near the cars and dispersion of dust in the atmosphere. For the numerical integration of the pollutant transport equation implicit alternating-triangular difference scheme was used. When constructing a difference scheme splitting of the transport equation is carried out that allows us to construct an efficient algorithm for solving a differential problem. Unknown value of the pollutant concentration at every step of splitting is determined by the explicit scheme – the method of point-to-point computation, which provides a simple numerical implementation of splitting equations. For numerical integration of the 3D equation for the velocity potential method of Richardson is applied. For numerical integration of the 2D equation for the velocity potential the method of total approximation is applied. The developed numerical models are the basis of established software package. On the basis of the constructed numerical models a computational experiment to assess the level of air pollution when demolition of coal dust from the gondola car was carried out. Findings. 3D, 2D numerical models that belong to the class «diagnostic models» were developed. These models take into account the main physical factors affecting the process of dust pollution dispersion in the atmosphere during transportation of bulk cargo, but require small costs of the computer time in the practice at the low and medium power machines. These models are used for serial calculations of various situations of scenarios related to issues of environmental protection and pollution intensity diagnostics for different weather conditions. Computational calculations to determine pollutant concentrations and formation of pollution zone near the cars with bulk cargo in «microscale» scale were submitted. Originality. 3D, 2D numerical models were created. They allow taking into account the relevant factors, influencing the process of pollutants dispersion in the atmosphere, and formation of the pollution zone during transport of bulk cargo by rail. Practical value. Efficient numerical models «diagnostic models» for rapid calculation of the atmosphere pollution level during transportation of bulk cargo by rail were considered. Models can be used in the development of environmental protection measures at the operation of rail transport. Proposed model allows calculating 3D, 2D hydrodynamics of wind flow and mass transfer process of pollutants in the atmosphere.